Infrastructure and Structural Change in the Lake Chad Region - Lebrand, Mathilde (World Bank, Washington, DC, 2022)
Access to infrastructure supports economic development through structural transformation. This paper investigates the links between investments in electricity, Internet, and transport infrastructure, in isolation and bundled, and economic development in the Lake Chad Region. Using data on the expansion of the paved road, electricity, and Internet networks over the past two decades and two instruments, it provides reduced-form estimates of the impacts of infrastructure investments on the sectoral composition of employment. Bundled infrastructure investments cause different patterns of structural transformation than isolated infrastructure investments. Bundled paved road and electricity investments is found to have reduced the agricultural employment share by 22 percentage points and increased the share of employment mostly in services. The paper then uses a spatial general equilibrium model to quantify the impacts of future regional transport investments, bundled with a large rural electrification program and trade facilitation measures to reduce border delays, on economic development in Nigeria, Cameroon, and Chad.